Prognosis for pregnancies with trisomy 16 confined to the placenta: A Danish cohort study. (16th December 2018) - Grau Madsen, Sandra; Uldbjerg, Niels; Sunde, Lone; Becher, Naja; ,; ,
Abstract: Objective: To evaluate the risk of adverse pregnancy outcome when trisomy 16 confined to the placenta is diagnosed and to identify possible prognostic markers for adverse outcomes in these pregnancies. Method: Registered cases ( n  = 49) of trisomy 16 diagnosed prenatally in Denmark from 1990 to 2013 were included. Results: Twenty‐five of the pregnancies intended to be continued had confined placental trisomy 16 mosaicism (CPM16). Adverse pregnancy outcome was seen in 17 CPM16 pregnancies (68%), ranging from mild small for gestational age (SGA) to fetal malformations and intrauterine demise. For cases ascertained by combined first trimester screening, the median concentration of pregnancy associated plasma protein A (PAPP‐A) was 0.17 MoM (IQR: 0.11 MoM). Adverse pregnancy outcome showed a trend toward an association with a high frequency of trisomic cells. Eight children (32%) were born at term with a normal birth weight and no malformations. Conclusion: The risk of adverse pregnancy outcome in case of CPM16 is correlated to ascertainment by combined first trimester screening and tends to be associated with a high frequency of trisomic cells in the placenta. We recommend that variables including ascertainment, the frequency of trisomic cells, and the maternal serum concentration of PAPP‐A are taken into consideration when evaluating the prognosis in CPM16 while acknowledging that these factors are strongly correlated. Abstract : What is already known about this topic? Case reports, large series, and literature reviews concerning outcome of placental trisomy 16 pregnancies have been published. Pregnancy outcome ranges from the birth of a normal child to severe fetal malformations. No reliable predictors for adverse pregnancy outcome have been identified even though several have been suggested, among these a high frequency of trisomic cells. What does this study add? This study is based on a prospectively registered cohort of consecutive placental trisomy 16 and therefore not biased by selection or publication. We present the pregnancy outcome in 25 unbiased cases with confined placental mosaicism for trisomy 16. Suggested predictors for outcome are ascertainment by combined first trimester screening and the frequency of trisomic cells in cultured chorionic villus cells.